Genotype and clinical phenotype in congenital generalized lipodystrophy type 1: analysis and literature review - SONG Zongxian, DONG Zhiya, LU Ziwen, LI Yanxiao, CHEN Ye (Zhenduanxue lilun yu shijian, 2022)
Objective: To explore the genotype and clinical phenotype of congenital generalized lipodystrophy type 1(CGL1), and to improve awareness of the disease. Methods: A patient with severe acanthosis nigricans was diagnosed as having CGL1, and the clinical information and results of laboratory and gene tests were analyzed. Five Chinese cases with CGL1 in the database were literaturally reviewed. Results: The patient was a girl(10 years and 11 months), who had significantly acanthosis nigricans and body subcutaneous fat loss. The examination of the girl showed hyperinsulinemia, impaired glucose tolerance, advanced bone age, low adiponectin and polycystic ovary. The compound heterozygous mutations were identified, which was c.646A>T:p.K216*(PVS1_Strong+ PM2+PM3 ( inherited from her father) and c.406G>A:p.G136R(PM3_Strong+PM1+PM2+PP3 (inherited from her mother) in AGPAT2 gene. The mutation of two gene loci could be pathogenic, which had not been reported in CNKI database. All 5 Chinese cases in CNKI database were reported before (including 2 males and 3 females, and age was between 66 days and 26 years old) showed the absence of adipose tissue, in which two patients presented severe acanthosis nigricans. Conclusions: The CGL1 is rare in Chinese population, and it should be considered as the patients present the acanthosis nigricans and absence of adipose tissue, and its diagnosis depends gene detection.